Instructional management of head teachers and its relation to teachers' commitment to teaching work / Shazali Hj Rosdi - Rosdi (Hj), Shazali (2012)
The purpose of this study was to determine which of the 10 leadership functionscontained in the Principal Instructional Management Rating Scale (PIMRS), as identified by Hallinger (1983), are demonstrated by the head teacher and the nine items in the Teachers’ Commitment to Teaching Work (TCTW) demonstrated by teachers at three different types of primary school in the district of Kuching. The schools involve in the study are government national school, religious school, and a missionary school. A number of 150 questionnaires were distributed to the target respondents of teachers from the respective schools. The results and findings presented in this study are based on the following Research Objectives in which it meant to determine teachers’ perception toward the Head Teachers’ Instructional Management. The study also wishes to investigate whether the head teachers’ Instructional Management role has any relation to the teachers’ commitment to teaching work. Alongside, it is also expected to examine the relative importance of head teachers’ Instructional Management towards teachers’ commitment to teaching work. The study also sought to determine if there would be a significant difference in teachers’ perceptions of the head teachers' instructional management roles as well as to investigate teachers’ commitment to teaching work that will contribute to enhance student achievement and the school outcomes at large. Descriptive statistics were used to identify which instructional management functions were being demonstrated frequently by the head teachers as the instructional leader cum instructional managers at school.